WOMEN AND NATURE IN TONI MORRISON'S BELOVED: AN ECOFEMINIST APPROACH - Niko Fediyanto (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2017)
WOMEN AND NATURE IN TONI MORRISON'S BELOVED: AN ECOFEMINIST APPROACH